Curriculum Innovation in Early Childhood Education: A Framework for Developmentally Appropriate Learning - Dybio Dompu Hot Asih; Jasael Simanullang; Atania Rosbina Br Bangun (Journal of Early Childhood Education Research, 2026)
Purpose: Early childhood education (ECE) serves as a foundational stage for children's holistic development, yet many programs continue to rely on conventional curricula that inadequately address children's diverse developmental needs. This study examines curriculum innovation and pedagogical advancement in ECE settings, with the aim of proposing a framework for developmentally appropriate practice (DAP) that integrates child-centered, progressive pedagogical approaches to support children's cognitive, social, and emotional development. Methodology: A qualitative case study design was employed across multiple early childhood education centers. Participants comprised early childhood teachers, curriculum coordinators, and school administrators directly involved in curriculum planning and implementation. Data were generated through semi-structured interviews, classroom observations, and document analysis of curriculum materials and lesson plans. Thematic analysis was used to identify patterns across curriculum innovation, pedagogical practices, and developmental appropriateness. Trustworthiness was established through data triangulation and member checking. Results: Findings reveal that curriculum innovation meaningfully enhances developmentally appropriate learning when grounded in child-centered pedagogical practices. Key innovative strategies identified include play-based learning, inquiry-based activities, and integrated thematic curriculum design. These approaches were associated with increased children's engagement, creativity, collaborative behavior, and problem-solving competencies. Teachers who adopted reflective practice and flexible curriculum adaptation demonstrated greater responsiveness to children's diverse developmental needs. Conclusions: Integrating curriculum innovation with progressive pedagogy offers a robust foundation for developmentally appropriate learning in early childhood settings. The proposed framework foregrounds child-centered environments, flexible curriculum structures, and reflective teaching as core principles. These findings carry practical implications for ECE educators, curriculum developers, and policymakers committed to improving the quality and responsiveness of early childhood education programs.